Recent advances in the development of methods for producing of porous titanium structures for medical applications - Mussabek, G.K.; Kalimoldayev, M.N.; Lysenko, V.; Dikhanbayev, K.K.; Baiganatova, Sh.B.; Amirkhanova, G.A. (Recent Contributions to Physics, 2020)
Due to the unique structural, mechanical and chemical properties, porous titanium is one of the promising biomaterials of modern medicine. Such properties as biocompatibility, strong mechanical strength, inertness make titanium and its alloys the main material of modern implantology in the field of orthopedics, traumatology and dentistry. The advantage of porous titanium biomaterials over dense metals is its better interconnection with bone tissue and providing better stabilization, which reduces the risk of implant loss. The connected pores contribute to tissue ingrowth and thus the attachment of the prosthesis to the surrounding bone becomes stronger, preventing the weakening of the implant. This article is a review on modern methods for obtaining porous titanium structures, discussions of its physical properties and descriptions of usage in biomedical applications. The paper provides information on both general methods for the formation of porous metal structures and a description of the most common modern methods for producing porous titanium structures. In summary, an assessment of the state of the problem of the development of methods for obtaining and studying the properties of structures of porous titanium is given and some predictions for its development in the future.